PERKEMBANGAN RELIGIOUS STUDIES DI BARAT (PANDANGAN ORIENTALIS DAN PEMAKNAAN ATAS AGAMA) - Rahman Mantu; Siti Aisa (Potret Pemikiran, 2019)
Western intellectuals are so concerned about religious studies. Their arguments are the subject of criticism and studies that continue to this day. the debate is about the position of religion whether as a way of life, belief, belief in something that is supernatural or religion as an object of study that can be interpreted with a logical scientific approach. This article will answer questions regarding the interpretation of religion by orientalists. Some names such as Max Muller to Charles Adams contributed thought. By using a comparative library analysis, the writer maps the ideas, ideas, and concepts of western scholars to the meaning of religion and the results of each orientalist express their thoughts that religion can function in accordance with the approach used, be it cultural, social, political , and economics. Keywords: Orientalist; West; Religion; Scientific; Confidence.  Intelektual Barat begitu memberikan perhatian terhadap studi agama. argumentasi mereka menjadi bahan kritikan dan kajian yang berlangsung terus menerus hingga hari ini. perdebatannya ada pada soal kedudukan agama apakah sebagai pedoman hidup, kepercayaan, keyakinan atas sesuatu yang gaib sifatnya ataukah agama sebagai objek studi yang bisa di maknai dengan pendekatan ilmiah yang logis. Artikel ini akan menjawab pertanyaan berkenaan dengan pemaknaan atas agama oleh para orientalis. Beberapa nama seperti Max Muller sampai Charles Adams memberikan sumbangsih pemikiran. Dengan menggunakan analisis kepustakaan yang komparatif, penulis melakukan pemetaan atas ide, gagasan, serta konsep para sarjanawan barat terhadap pemaknaan atas agama dan didapati hasilnya masing-masing orientalis mengemukakan pikirannya bahwa agama bisa berfungsi sesuai dengan pendekatan yang digunakan, baik itu budaya, sosial, politik, maupun ekonomi. Kata kunci: Orientalis; Barat; Agama; Ilmiah; Keyakinan